2018
DOI: 10.3233/bmr-171066
|View full text |Cite
|
Sign up to set email alerts
|

Single-dose intra-articular corticosteroid injection prior to platelet-rich plasma injection resulted in better clinical outcomes in patients with knee osteoarthritis: A pilot study

Abstract: According to our results, IA MP injection prior to PRP injection resulted in significantly better clinical outcomes compared to PRP and MP injections alone in patients who had mild to moderate knee OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…The authors have pointed out that the lack of control group, small sample size and lack of morphological assessments are among their study limitations [57]. As reported in a recent study, intra-articular injection of corticosteroids prior to PRP injection resulted in better outcomes in patients with mild to moderate OA [58]. Aside from studies including patients with knee OA, some randomized trials are also existed about other affected tissues like hip and ankle.…”
Section: Platelet-rich Plasmamentioning
confidence: 99%
“…The authors have pointed out that the lack of control group, small sample size and lack of morphological assessments are among their study limitations [57]. As reported in a recent study, intra-articular injection of corticosteroids prior to PRP injection resulted in better outcomes in patients with mild to moderate OA [58]. Aside from studies including patients with knee OA, some randomized trials are also existed about other affected tissues like hip and ankle.…”
Section: Platelet-rich Plasmamentioning
confidence: 99%
“…PRP was reported as better in terms of clinical improvement compared to oral NSAID administration [161], as synergistic and protective, when added to methylprednisolone [150] and comparable to HA and corticosteroids after three months, superior to both the other treatments in the long-term [149].…”
Section: Knee Osteoarthritismentioning
confidence: 92%
“…In addition, a pilot study evaluating the utility of combining CS and PRP showed a synergistic effect, with significantly lower WOMAC (at 1 and 3 months) and VAS (at 1, 3, and 6 months) scores in the combined group compared to PRP or CS alone. However, the benefits were no longer apparent at 12 months postinjection [34]. Based on these results, PRP may be a more effective treatment option for patients with moderate knee OA than CS with respect to pain relief and quality of life, and while more research is needed, the two interventions may have a synergistic effect at pain and disability reduction.…”
Section: Comparison To Other Treatments In Oamentioning
confidence: 92%